Transformation of Frontier National Parks into Tourism Sites. The North Andean Patagonia Experience (1934-1955) - Vejsbjerg, Laila (2014)
Tourism policies for peripheral regions of Argentina reinforced the inner-colonialism of the national territories during the period between the 1930 and the 1950 decades. Two models for tourism development (elite and social tourism) were contrasted in the first national park created in South America, the Nahuel Huapi National Park, and its correlated centre San Carlos de Bariloche. The main results obtained were: 1) The cultural landscape and the activity linked to the leisure and free time were used strategically for the citizens? education; 2) In its beginnings, nature conservation was associated with the imposition of the frontier itself and; 3) Populating policies constituted a problematic factor for the development of tourism.